REMOTE TRAINING OF STUDENTS TO PARTICIPATE IN THE INFORMATION TECHNOLOGY OLYMPIAD - Voitovych, Ігор; Pavlova, Наталія; Shrol, Тетяна; Poliukhovych, Наталія; Franchuk, Наталія (Journal of Information Technologies in Education (ITE), 2025)
The article examines the student Olympiad in information technology, reveals the process of preparing secondary school students for the Olympiad. For this purpose, theoretical, empirical, and statistical research methods were used. The works of domestic and foreign scientists on working with gifted students and involving them in in-depth study of the information technology industry are analysed. The process of organising and conducting a student Olympiad in information technology is modelled, the Olympiad tasks are studied, and on this basis the principles of preparing students for participation in intellectual competition are considered. The relevance of involving students in the Olympiad in information technology, whose participants demonstrate the skills of solving non-standard problems using application software and web technologies, is substantiated. In order to effectively prepare students for the Olympiad, a distance course was designed and implemented on the Moodle LMS platform, taking into account the didactic principles and methods of blended learning. The course structure includes three blocks: informational, activity, and reflective. The article describes the methodological work of the tutor and the educational and cognitive activities of students, as well as the results of their training and final tasks. The results of the course approbation in the form of final task solving and questionnaires are presented. It is concluded that students have expanded their general awareness of information technology, improved their skills in working with application software and Web technologies, developed the ability to select non-standard solutions, concentrate on the task and the process of solving it, and developed the readiness to acquire knowledge independently and apply it in new situations. At the same time, the results of the final works showed that it is worth focusing on tasks that develop skills in Excel and Access and broaden awareness of web technologies. Also, the students' responses to their participation in the developed course indicated their interest in this form of preparation for the Olympiad, as it successfully combines modern methods and techniques, selects tasks from all sections of the Olympiad, and provides a sufficient number of samples.